Identifying the best regimen for primary eradication of Helicobacter pylori: analysis of 240 cases. Issue 11 (7th October 2020) - Chen, Yao; Liu, Qingyi; Hu, Fulian; Ma, Jizheng
Abstract: The treatment regimen for the eradication of Helicobacter pylori may be best when therapy is susceptibility guided. However, it is unrealistic to use a strategy based on susceptibility testing to prioritize therapy for every patient in China. Empirical therapy of H .  pylori is still widely used. The study was designed to discuss the best first‐line treatment regimen depending on empirical therapy. The focal point of the study was the optimal length of the therapy. Also, the selection of antibiotics was discussed in the article. This was a prospective, randomized, non‐inferiority trial. H .  pylori ‐infected patients who have no previous eradication therapy were randomly assigned to the following: 20 mg of rabeprazole, 1000 mg of amoxicillin, 500 mg of clarithromycin, and 220 mg of bismuth potassium citrate (BACPPI), administered twice a day for 10 or 14 days. The efficacy, side effects, and remission rate of clinical symptoms were determined. A total of 240 subjects were included in the study. The eradication rate with 14 and 10 days was essentially identical in both intention‐to‐treat (90.83% [95% CI, 86%–96%] vs. 87.50% [95% CI, 82%–93%]) and per‐protocol (94.78% [95% CI, 91%–99%] vs. 92.11% [95% CI, 87%–97%]) analyses. Loss of appetite and belching symptoms were significantly better in the BACPPI‐10 group than those in the control group after treatment. Side effects were generally mild and similar between groups. Our results showed that a 10‐day amoxicillin–clarithromycin‐containing bismuth quadruple therapy may be recommended for the primary empirical treatment of H .  pylori infection in Beijing, China. Abstract : 10‐day amoxicillin–clarithromycin‐containing bismuth quadruple therapy may be recommended for the primary empirical treatment of Helicobacter pylori infection in China. The 14‐day therapy is expensive, uncomfortable for the patients, and has an increased risk of side effects. The 10‐day therapy was not inferior to the 14‐day therapy in terms of efficacy.